2015
DOI: 10.4172/2157-7439.s6-008
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Characterization of Silver Nanoparticles (Snps) by using Leaf Extracts of Ocimum Sanctum L (Tulsi) and Study of its Antibacterial Activities

Abstract: The present study aimed to synthesis of SNPs (Silver Nanoparticles) or (Green-Silver) in aqueous medium using leaf extracts of Ocimum sanctum L. The synthesized silver nanoparticles (SNPs) were characterized by the different techniques such as UV-vis Spectrophotometer, XRD, FTIR and TEM. The synthesis of silver nanoparticles were confirmed due to the SPR optical absorption band peak at ~440 nm by UV-vis spectrophotometer, nearly 15-45 nm in diameter with spherical in shape by TEM, high crystalline with the Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…Nanotechnology is the field of materials science to develop the most active nanomaterials for the therapeutic potential of numerous diseases [1]. The prepared nanoparticles exhibits several physiochemical properties and characteristics such as size, morphology and distribution [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanotechnology is the field of materials science to develop the most active nanomaterials for the therapeutic potential of numerous diseases [1]. The prepared nanoparticles exhibits several physiochemical properties and characteristics such as size, morphology and distribution [2].…”
Section: Introductionmentioning
confidence: 99%
“…Silver has been recognized to inhibit microbes for medical and industrial application and it has been mainly used in the medical and pharmaceutical industry for preparing topical ointments to prevent infection against burn and wounds. Moreover, silver metal has been considered as a toxic material that can cause deleterious toxicity against several types of cancer cells [1]. Synthesis and characterization of silver nanoparticles from the medicinal plant or extracts are recently shown to be the greatest approach to develop selective drug delivery for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These phenolic compounds have pharm logical, medicinal, antibacterial, and an antioxidant effect [21]. Bindhani and Panigrahi suggested that the reducing property of the OS leaf extract was associated with their specific phenolic composition such as eugenol [22]. Recently, Apsana et al also reported the reduction of Ca and Co metal ions using OS leaf extract and further it is confirmed that the possible reducing agent is eugenol by characterizing OS leaf extract using ultraviolet (UV) spectral analysis [23].…”
Section: Introductionmentioning
confidence: 78%
“…Among the various green techniques, the use of plant leaf extract provides an economic viable and ecofriendly path for a well-regulated synthesis of nanostructures with well-defined morphology [26,27]. Until now, various plant extracts such as P. trifoliate fruit extract [28], Ocimum Sanctum L (Tulsi) [29], Ocimum Tenuiflorum (black Tulsi) [30] and Ficus benghalensis (Banyan tree) [31] etc. have been utilized for the preparation of nanostructures.…”
Section: Introductionmentioning
confidence: 99%